Peran Artificial Intelligence dan Self-Directed Learning terhadap Strategi Belajar Mahasiswa Pendidikan Ekonomi - Septi Anesia Purnama; Jean Elikal Marna (Universitas Negeri Makassar, 2026)
This study aims to examine the role of Artificial Intelligence and Self-Directed Learning in the learning strategies of Economics Education students at Padang State University. This study employed an associative quantitative approach involving 87 students selected through proportional random sampling from a population of 646 active students. Data were collected using a questionnaire and analyzed using multiple linear regression. The results indicate that the use of Artificial Intelligence does not have a significant effect on students’ learning strategies. On the other hand, Self-Directed Learning has a positive and significant influence on learning strategies. Furthermore, Artificial Intelligence and Self-Directed Learning interact synergistically in influencing students’ learning strategies, accounting for 37.8% of the variance in learning strategies. These results indicate that students’ ability to independently monitor and direct their learning journey has a greater influence on determining learning strategies than simply relying on Artificial Intelligence technology.